A. P. Lerner at Sixty - Samuelson, Paul A. (Review of Economic Studies, 1964)
Journal Article A. P. Lerner at Sixty Get access Paul A. Samuelson Paul A. Samuelson Massachusetts Institute of Technology Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 31, Issue 3, June 1964, Pages 169–178, https://doi.org/10.2307/2295906 Published: 01 June 1964